Harmony Search for Balancing Two-sided Assembly Lines - Hindriyanto Dwi Purnomo; Hui-Ming Wee; Hsin Rau (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
Two-sided assembly lines balancing problems are important problem for large-sized products such as cars and buses, in which, tasks operations can be performed in the two sides of the line. In this paper, Harmony Search algorithm is proposed to solve two-sided assembly lines balancing problems type-I (TALBP-I). The proposed method adopts the COMSOAL heuristic and specific features of TALBP in the Harmony operators – the harmony memory consideration, random selection and pitch adjustment – in order to maintain the local and global search. The proposed method is evaluated based on 6 benchmark problems that are commonly used in TALBP. The experiment results show that the proposed method work well and produces better solution than the heuristic method and genetic algorithm.